Digest: Habitat seasonality drives evolutionary change in plasticity in Bicyclus butterflies - van Bergen, Erik (2023)
Can changes in plasticity evolve in populations in response to local conditions? Zhen et al. addressed this question using populations of Bicyclus butterflies from Cameroon. The results of the study suggest that local adaptation in these African butterflies involved changes in the degree of plasticity, such that stronger responses to temperature were found in populations from habitats with stronger seasonal fluctuations. Interestingly, differentiation in reaction norms occurred despite high levels of gene flow among populations, indicating a small number of loci contributing to evolved differences in plasticity.